2004
DOI: 10.1007/s10350-004-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multivisceral Resection and Standard Operation for Locally Advanced Colorectal Cancer: Analysis of Prognostic Factors for Short-Term and Long-Term Outcome

Abstract: For locally advanced colorectal cancer, the long-term outcome after multivisceral resection is comparable to that after the standard operation. However, it should be recognized that multivisceral resection is associated with higher postoperative morbidity. In addition, a reduction in the incidence of blood transfusion may contribute to improving patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
123
3
17

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 38 publications
15
123
3
17
Order By: Relevance
“…Nakafusa et.al. reported that the rate of ileus in the multivisceral resection group was significantly higher than that in the single organ resection group in addition to infectious complications (14). In our study, as two cases of ileus and seven cases of infectious complications were observed as postoperative complication, we need to take into account the occurrence of ileus and infectious complications probably due to the large dead space after multivisceral resection.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Nakafusa et.al. reported that the rate of ileus in the multivisceral resection group was significantly higher than that in the single organ resection group in addition to infectious complications (14). In our study, as two cases of ileus and seven cases of infectious complications were observed as postoperative complication, we need to take into account the occurrence of ileus and infectious complications probably due to the large dead space after multivisceral resection.…”
Section: Discussionmentioning
confidence: 77%
“…So, careful follow-up to diagnose early recurrence, especially within two years, would be required. As Nakafusa et al previously reported that only multivisceral resection was an independent factor for overall postoperative complications (14), extended en bloc multivisceral resection might involve serious complications, leading to an increase in morbidity and mortality. In previous reports, postoperative morbidity and mortality rates after mutivisceral resection tend to be higher ranging from 28.0 to 43.7% (2,8,12,(15)(16)(17) and ≥13% (5,7,12,18), respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Os principais fatores que pioram o prognóstico das ressecções alargadas são comprometimento linfonodal, transfusão sanguínea e violação do tumor. Embora a morbidade pós-operatória seja maior que a cirurgia convencional, a abordagem em monobloco reduz a incidência de sangramento e contribui para melhores resultados, apresentando índices de recidiva local, tempo livre de doença e sobrevida global semelhantes aos casos que não requerem ressecção multivisceral 7,16 .…”
Section: Discussionunclassified
“…Reportedly, histologic tumor infiltration is demonstrated in 39-84% of cases in which the tumor is found to be adherent to the adjacent viscera whereas the rest represent inflammatory adherence [4,[6][7][8][12][13][14][15][16][17]. Any attempt to separate the carcinoma from adherent organs may lead to tearing or transection of the tumor with the risk of intraoperative dissemination of tumor cells, resulting in early local recurrence [1,4,6,15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study confirmed that T4 stage is an important independent prognostic factor [11]. On the contrary, many investigators have reported the feasibility of the en bloc resection [4,6,7,12] and some have shown a fairly good long-term prognosis [13,14]. However, there were few studies investigating the prognostic significance of tumor invasion to adjacent organs after en bloc resection in locally advanced colon cancer.…”
Section: Introductionmentioning
confidence: 99%